Stabilization of chaotic quaternion-valued neutral-type neural networks via sampled-data control with two-sided looped functional approach - Song, Qiankun; Wu, Qian; Liu, Yurong (Nonlinear Analysis: Modelling and Control, 2024)
The quaternion-valued neutral-type neural networks (QVNTNNs) stability problem through designing sampled-data controller is investigated in this paper. A main stability criterion of the considered neural networks (NNs) is obtained in the form of linear matrix inequalities (LMIs) based on the two-sided looped functional method. The effectiveness of the criterion is shown by a numerical example. It needs to be emphasized that the considered QVNTNNs model in this paper is not broken down into real-valued or complex-valued models in stability analysis, and the acquired criterion holds for both real-valued and complex-valued NNs.